Relation between broodstock number and spawning frequency and egg production of humpback grouper (Cromileptes altivelis) - Syaifudin, M.; Aliah, R.S.; Muslim, .; Sumantadinata, K. (Indonesian Society of Scientific Aquaculture (ISSA), 2007)
This study was performed to determine spawning frequency, number of ovulated egg and spawning time of humpback grouper (Cromileptes altivelis) broodstock in hatchery. Broodstock of 20-83 fish in weight of 1.5-2.0 kg were reared in circular concrete tank 225 m3. The results showed that increasing in number of broodstock increases spawning frequency (R2= 0.694), and ovulated eggs number was also increased (R2= 0.828). Spawning of humpback grouper can occur in the third to fourth week in every month. Keywords: reproductive biology, spawning, Cromileptes altivelis ABSTRAK Penelitian ini bertujuan untuk mengetahui frekuensi pemijahan, jumlah telur dan waktu pemijahan populasi induk ikan kerapu tikus (Cromileptes altivelis) di hatchery. Jumlah induk yang bervariasi antara 20-83 ekor dengan ukuran 1,5-2 kg ditempatkan dalam bak beton bulat, kapasitas 225 m3. Hasil penelitian ini menunjukkan bahwa dengan bertambahnya jumlah induk, maka frekuensi pemijahan yang diperoleh juga semakin meningkat (R2=0,694), dan produksi telur juga semakin meningkat (R2=0,828). Pemijahan kerapu tikus dapat berlangsung setiap bulan, di mana waktu pemijahan terjadi pada kuarter keempat hingga kuarter ketiga. Kata kunci: Biologi reproduksi, Pemijahan, Cromileptes altivelis